2013
DOI: 10.1016/j.conb.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the neurobiology of nicotine dependence using genetically engineered mice

Abstract: This review article provides an overview of recent studies of nicotine dependence and withdrawal that used genetically engineered mice. Major progress has been made in recent years with mutant mice that include knockout and gain-of-function of specific neuronal nicotinic acetylcholine receptor (nAChR) subunit genes. Nicotine exerts its actions by binding to these neuronal nAChRs, which consist of five subunits. The different nAChR subunits that combine to compose a receptor determine the distinct pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Mice with genetic deletion of different nAChR subunits will be valuable for dissecting the mechanism by which nicotine influences aggressive behavior (Changeux, 2010; Stoker and Markou, 2013). A recent study investigating how social behavior is regulated by cholinergic and norepinephrine transmission in the prefrontal cortex (PFC) used β2 subunit knockout mice (β2 −/− ) in a social interaction task, which included a measure of aggressivity (Coura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mice with genetic deletion of different nAChR subunits will be valuable for dissecting the mechanism by which nicotine influences aggressive behavior (Changeux, 2010; Stoker and Markou, 2013). A recent study investigating how social behavior is regulated by cholinergic and norepinephrine transmission in the prefrontal cortex (PFC) used β2 subunit knockout mice (β2 −/− ) in a social interaction task, which included a measure of aggressivity (Coura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area has generally focused on (1) genes related to nicotine metabolic enzymes, and (2) genes related to neurotransmitters involved in the brain's dopaminergic reward system [8]. For example, recent studies have identified genetic polymorphisms associated with nicotine dependence and the efficacy of smoking cessation treatments, including variants in CYP2A6 (encoding nicotine-metabolizing enzyme cytochrome P450 2A6) [9], the CHRNA5/CHRNA3/CHRNB4 gene cluster (encoding neuronal nicotinic acetylcholine receptor subunits) [10,11,12], and several other loci [9,13]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, genome-wide studies identified associations between lung cancer and several single nucleotide polymorphisms within the gene cluster encoding the ␣3, ␣5, and ␤4 nAChR subunits (10). Additionally, activation of the ␣3␤4 nAChR, a predominant subtype expressed in sympathetic and parasympathetic neurons of mammalian autonomic ganglia (11)(12)(13), is known to be associated with nicotine addiction and drug abuse (14,15). However, our understanding of the physiological relationship is limited.…”
mentioning
confidence: 99%